1999
DOI: 10.1111/j.1471-0307.1999.tb02069.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of thermophilic spore forming bacilli in milk during the manufacture of low heat powders

Abstract: The survival and growth of Bacillus stearothermophilus and Bacillus licheniformis, naturally present (30–300 colony forming units/ml) in late season skim milk, was monitored in a three effect evaporator during low heat skim milk powder manufacture. Substantial growth was shown to occur in the preheating stages prior to direct steam heating. A typical heat treatment (77°C, 15 s) used in the manufacture of low heat powder did not inactivate the bacteria, which continued to grow in the heater. The importance of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 7 publications
1
69
1
1
Order By: Relevance
“…isolates from SMP samples. The presence of thermophilic strains of G. stearothermophilus, B. licheniformis and B. subtilis has been confirmed in both raw milk and milk powders in numerous instances (Phillips & Griffiths, 1990, Crielly et al 1994, Murphy et al 1999. Pre-identification of Bacillus species isolated from UHT milk:…”
Section: Lactose Fermentation Testmentioning
confidence: 99%
“…isolates from SMP samples. The presence of thermophilic strains of G. stearothermophilus, B. licheniformis and B. subtilis has been confirmed in both raw milk and milk powders in numerous instances (Phillips & Griffiths, 1990, Crielly et al 1994, Murphy et al 1999. Pre-identification of Bacillus species isolated from UHT milk:…”
Section: Lactose Fermentation Testmentioning
confidence: 99%
“…The presence of spores of thermophilic bacilli are a common problem during milk powder manufacture (32). Thermophilic spores from bacteria such as Geobacillus spp.…”
mentioning
confidence: 99%
“…These are Geobacillus stearothermophilus (formerly Bacillus stearothermophilus) strain A, Anoxybacillus flavithermus (strains B, C and D), Bacillus licheniformis (strains F and G) and Bacillus subtilis. The presence of thermophilic strains of G. stearothermophilus, B. licheniformis and B. subtilis has been confirmed in both raw milk and milk powders in numerous instances (Reddy et al 1975;Stadhouders et al 1982;Chopra & Mathur, 1984;Kwee et al 1986;Phillips & Griffiths, 1986;Phillips & Griffiths, 1990;Crielly et al 1994;Murphy et al 1999). Significantly, strains of A. flavithermus, which were originally isolated from a hot spring in New Zealand (Heinen et al 1982) and subsequently from hot springs in Yellowstone National Park, USA (Nold et al 1996) and Turkey (Beldü z et al 2000), have recently been conclusively identified in milk powders (Flint et al 2001;Ronimus et al 2003;Rueckert et al 2004).…”
mentioning
confidence: 97%
“…Thermophilic sporeforming bacterial contamination is routinely monitored despite there being no evidence of their involvement in human disease ; but they are a useful indicator organism of good hygiene practices within milk powder producing factories and for downstream food processing requirements (Stadhouders et al 1982;Kwee et al 1986;Murphy et al 1999). The milk industry is usually required to store samples of powder products for a number of years (commonly 2 to 3), after which they are usually destroyed, thus precluding the analysis of the survival of contaminants in powder stored for a long period.…”
mentioning
confidence: 99%